Preparation method of copper nanosheet and copper nanosheet
By using environmentally friendly solvents and soluble halide ions in the preparation of copper nanosheets, combined with the use of reducing agents and amine substances, the problems of environmental pollution and product impurity in the prior art are solved, and efficient and environmentally friendly copper nanosheet preparation is achieved to meet the needs of high-end applications.
Patent Information
- Application Number
- CN202411758832.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
AI Technical Summary
The existing liquid phase reduction method for preparing copper nanosheets has problems such as environmental pollution, high production costs, unclean product surfaces, low purity and proportions, and it is difficult to meet the needs of high-end application fields.
Copper salt, protective agent, soluble bromine salt or iodine salt are used to dissolve in environmentally friendly solvents. By adding reducing agent, amine substances and alkalis, the reaction conditions are controlled to achieve efficient preparation of copper nanosheets.
It significantly reduces environmental pollution and waste emissions, improves the purity and yield of copper nanosheets, and achieves flexible particle size adjustments to meet the needs of different industrial applications.
Smart Images

Figure CN119549732A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of metal nanomaterials, and specifically to a preparation method of a copper nanosheet and a copper nanosheet. Background Art
[0002] Copper nanosheets, as an important nano-scale material, have shown broad application potential in many high-tech fields such as electronic devices, optical technology, and catalytic reactions due to their unique physical and chemical properties. Their nano-scale sheet structure gives the material a large specific surface area and excellent interface properties, which make copper nanosheets perform well in many applications. For example, copper nanosheets have been widely used in thermal conductive materials in the field of electronic packaging, conductive ink formulations in printed circuit board manufacturing, and electrode structures of optoelectronic display components due to their high electrical conductivity and interfacial reaction activity, effectively improving the comprehensive performance and operational reliability of electronic equipment.
[0003] However, it is worth noting that copper, as a typical face-centered cubic crystal material, naturally tends to grow into a three-dimensional tightly packed particle structure. Therefore, it is undoubtedly a challenging task to achieve the controllable growth of copper materials along the two-dimensional direction to prepare high-quality sheet-like nanomaterials.
[0004] At present, there are two main methods for preparing copper nanosheets: physical method and chemical method. Among them, the liquid phase reduction method in the chemical method has become the mainstream means of preparing copper nanosheets because of its simple operation and low dependence on professional equipment. However, the current liquid phase reduction method for preparing copper nanosheets also has significant disadvantages, mainly including: large consumption of organic reagents, which not only increases production costs, but also causes serious pollution to the environment; dependence on long-chain capping agents, limited by solubility constraints, cannot be synthesized in large quantities, affecting preparation efficiency; using oil phase solvents, the product surface is not clean, subsequent treatment is complicated, and the amount of sewage discharged is large; in addition, the proportion and purity of the resulting copper nanosheets are low, which is difficult to meet the strict requirements of high-end application fields. Summary of the invention
[0005] In order to overcome the defects of the prior art, the present invention aims to develop a new method for preparing copper nanosheets that is efficient, environmentally friendly, and has adjustable particle size.
[0006] A first aspect of the present invention provides a method for preparing copper nanosheets, comprising:
[0007] (1) dissolving a copper salt, a protective agent, and a capping agent in a first solvent to obtain a first mixed solution;
[0008] (2) adding a reducing agent to the first mixed solution to react, and the ratio of copper nanosheets in the obtained product is 80% to 99%;
[0009] Wherein, the capping agent is a soluble bromide salt or iodine salt.
[0010] According to the method of the first aspect, in step (1), the copper salt is selected from one or more of CuSO4·5H2O, Cu(NO3)2·3H2O, CuCl2, CuBr2, and Cu(HCOO)2·4H2O;
[0011] In step (1), the protective agent is a surfactant, preferably one or more selected from PVP, polyethyleneimine, and polyethylene glycol;
[0012] In step (1), the first solvent is alcohol and / or water, preferably ethylene glycol and / or water; and / or
[0013] In step (2), the reducing agent is selected from one or more of ascorbic acid, glucose, sodium hypophosphite, sodium borohydride, and hydrazine hydrate.
[0014] According to the method of the first aspect, in step (2), it also includes adding an amine substance and / or a base to the first mixed solution;
[0015] Preferably, the amine substance is selected from one or more of triethylenetetramine, diethylenetriamine, tetraethylenepentamine, isopropanolamine, oleylamine, ethylenediamine, ethanolamine, polyethyleneimine, 2-amino-2-methyl-1-propanol, triethylenediamine, and ammonia water; and / or
[0016] Preferably, the base is selected from one or more of NaOH and KOH, more preferably NaOH.
[0017] According to the method of the first aspect, in step (2), the reducing agent, the optional amine substance, and the optional base are dissolved in a second solvent to obtain a second mixed solution, and then the second mixed solution is added to the first mixed solution;
[0018] Preferably, the second solvent is one or more of water and ethylene glycol, more preferably water.
[0019] According to the method of the first aspect, in step (2), the second mixed solution is added by pouring or pumping, preferably by pumping;
[0020] More preferably, the pumping speed is 2 to 20 mL / min.
[0021] According to the method of the first aspect, in step (2), the reaction temperature is 60 to 120°C.
[0022] According to the method of the first aspect, the molar ratio of the capping agent to the copper salt is 1:(2-6);
[0023] The molar ratio of the reducing agent to the copper salt is (1-5):1;
[0024] The mass ratio of the copper salt to the protective agent is 1:(0.1-0.6)
[0025] The molar ratio of the amine substance to the copper salt is 1:(0.25-8).
[0026] According to the method of the first aspect, the method further comprises the following steps:
[0027] (3) washing and drying the prepared copper nanosheets;
[0028] Preferably, the washing comprises washing the prepared copper nanosheets with 5% hydrochloric acid, deionized water and ethanol in sequence; after washing, drying is performed under vacuum or inert gas protection.
[0029] The second aspect of the present invention provides a copper nanosheet, which is prepared by the method of the first aspect.
[0030] According to the copper nanosheet of the second aspect, the particle size of the copper nanosheet is 100 nm to 50 μm, preferably 400 nm to 20 μm.
[0031] The preparation method of the present invention has but is not limited to the following beneficial effects:
[0032] 1. In the preparation process of the present invention, environmentally friendly solvents (such as ethylene glycol, water, etc.) and halogen ions (from soluble bromide salts or iodide salts) are specially selected as end-capping agents. This not only significantly reduces environmental pollution and waste emissions in the production process, but also avoids the use of long-chain end-capping agents to ensure the cleanliness of the copper nanosheet surface and help improve the purity and yield of the copper nanosheet. The clean copper nanosheet surface is easy to carry out a variety of chemical modifications including antioxidant modification, which not only improves stability, but also opens up more possibilities for applications in the fields of electronics, catalysis, biomedicine, etc.
[0033] 2. By finely controlling the reaction conditions (including key process parameters such as solvent selection, reaction temperature, reaction time, reactant concentration and ratio), the present invention also achieves flexible adjustment of the copper nanosheet particle size in the range of 100 nm to 50 μm. This feature enables the copper nanosheets prepared by the present invention to better meet the diverse requirements of nanomaterial performance in different industrial application scenarios.
[0034] 3. The raw materials used in the method of the present invention are easy to obtain and have low production costs. In addition, the method is highly efficient and scalable, which makes it possible to achieve large-scale and continuous production of copper nanosheets, thereby effectively meeting the growing demand for high-performance nanomaterials in the industrial field. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1A flow chart of preparing copper nanosheets in Example 1 is shown.
[0036] Figure 2 The SEM image of the copper nanosheets prepared in Example 1 is shown, and the average sheet diameter is 19 μm.
[0037] Figure 3 The XRD spectrum of the copper nanosheets prepared in Example 1 is shown.
[0038] Figure 4 The SEM image of the copper nanosheets prepared in Example 2 is shown, and the average sheet diameter is 13 μm.
[0039] Figure 5 The SEM image of the copper nanosheets prepared in Example 3 is shown, and the average sheet diameter is 10 μm.
[0040] Figure 6 The SEM image of the copper nanosheets prepared in Example 4 is shown, and the average sheet diameter is 7 μm.
[0041] Figure 7 The SEM image of the copper nanosheets prepared in Example 5 is shown, and the average sheet diameter is 3 μm.
[0042] Figure 8 The SEM image of the copper nanosheets prepared in Example 6 is shown, and the average sheet diameter is 10 μm.
[0043] Fig. 9 The SEM image of the copper nanosheets prepared in Example 7 is shown, and the average sheet diameter is 12 μm.
[0044] Fig.10 The SEM image of the copper nanosheets prepared in Example 8 is shown, and the average sheet diameter is 8 μm. DETAILED DESCRIPTION
[0045] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.
[0046] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0047] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0048] The present invention provides a method for preparing copper nanosheets, comprising:
[0049] (1) dissolving a copper salt, a protective agent, and a capping agent in a first solvent to obtain a first mixed solution;
[0050] (2) adding a reducing agent to the first mixed solution to carry out a reaction, wherein the ratio of copper nanosheets in the obtained product is higher than 80%, preferably 80% to 99%;
[0051] Wherein, the capping agent is a soluble bromide salt or iodine salt.
[0052] The present invention provides a method for preparing copper nanosheets, which uses halogen ions as capping agents, overcomes the defect of using long-chain capping agents in the prior art that is limited by solubility, improves the synthesis efficiency, and has now achieved a high efficiency of producing 10g of copper nanosheets per 100mL of solvent, and realizes flexible adjustment of the copper nanosheet particle size within the range of 100nm to 50μm through the regulation of process parameters. The copper nanosheets prepared by the method of the present invention have a high proportion of copper nanosheets in the product (up to more than 90%), high surface cleanliness, and uniform particle size distribution, and can realize efficient large-scale production of copper nanosheets.
[0053] The end-capping agent of the present invention is a soluble bromide salt or a soluble iodide salt, and the bromide salt or iodide salt can be an inorganic salt or an organic salt, for example, potassium bromide, ammonium bromide, sodium bromide, potassium iodide, sodium iodide, CTAB, etc. In one embodiment, in step (1), the copper salt is selected from one or more of CuSO4·5H2O, Cu(NO3)2·3H2O, CuCl2, CuBr2, Cu(HCOO)2·4H2O;
[0054] In step (1), the protective agent is a surfactant, preferably one or more selected from PVP, polyethyleneimine, and polyethylene glycol;
[0055] In step (1), the first solvent is alcohol and / or water, preferably ethylene glycol and / or water; and / or
[0056] In step (2), the reducing agent is selected from one or more of ascorbic acid, glucose, sodium hypophosphite, sodium borohydride, and hydrazine hydrate.
[0057] In the method of the present invention, a protective agent is added to prevent particle agglomeration, and a green solvent is used to provide a suitable environment for the reaction, thereby improving the cleanliness of the product surface and being environmentally friendly.
[0058] In one embodiment, step (2) further comprises adding an amine substance and / or a base to the first mixed solution; preferably, the amine substance is selected from one or more of triethylenetetramine, diethylenetriamine, tetraethylenepentamine, isopropanolamine, oleylamine, ethylenediamine, ethanolamine, polyethyleneimine, 2-amino-2-methyl-1-propanol, triethylenediamine, and ammonia water; and / or
[0059] Preferably, the base is selected from one or more of NaOH and KOH, more preferably NaOH.
[0060] In the further optimization of step (2) of the present invention, an amine substance can be additionally added to the first mixed solution to improve the controllability and product quality of the copper salt reduction process for preparing copper nanosheets. The reduction of copper salts in aqueous solutions or organic solvents usually undergoes a continuous transformation process from divalent copper ions (Cu2+) to monovalent copper ions (Cu+), and finally to zero-valent copper (Cu). In the traditional reduction system, if only a simple reducing agent is relied on and halogen ions are used as capping agents, although the growth of nanoparticles can be regulated to a certain extent, the presence of halogen ions often promotes the combination of monovalent copper ions (Cu+) and halogens to form precipitates, such as CuI or CuBr. The formation of this precipitate reduces the number of effective monovalent copper ions available for reduction in the system, and also leads to the non-uniformity of the reduction reaction rate - this non-uniformity further leads to a problem: copper ions that have not formed a precipitate will be reduced first, while the part that has formed a precipitate will be reduced slowly, and may not even be completely reduced to a zero-valent state, thereby affecting the morphology, purity and uniformity of the copper nanosheets. In order to solve this problem, the present invention introduces amine compounds as additives. The amine group (such as -NH) in the amine substance can be tightly combined with the monovalent copper ion (Cu+) due to its strong coordination ability to form a stable complex. The formation of this complex effectively inhibits the combination of monovalent copper ions with halogen ions or other anions, thereby preventing the production of precipitation. This coordination effect not only ensures the continued effectiveness of monovalent copper ions in the reaction system, but the presence of the amine group also makes the entire reduction process more stable and controllable. Specifically, the amine group slows down the trend of monovalent copper ions to transform into precipitates, so that more copper ions can be reduced to zero-valent copper in a more uniform and gradual manner, promoting the rapid formation of nanocrystal nuclei. At the same time, due to the coordination effect of the amine group, the rapid aggregation of zero-valent copper atoms is inhibited to a certain extent, thereby meeting the ideal condition of "fast nucleation and slow growth" in the growth dynamics of nanocrystals. This condition helps to generate copper nanosheets with high purity, regular shape and uniform particle size, thereby increasing the proportion of copper nanosheets in the prepared product. In addition, a base can be added to the first mixed solution to increase the solubility of the reducing agent and simultaneously regulate the pH. The addition of base can promote the deprotonation of the reducing agent and enhance the nucleophilic reaction ability of the reducing agent, thereby enhancing the reducing property of the reducing agent and further improving the reaction efficiency.
[0061] In one embodiment, in step (2), the reducing agent, the optional amine substance, and the optional base are dissolved in a second solvent to obtain a second mixed solution, and then the second mixed solution is added to the first mixed solution;
[0062] Preferably, the second solvent is one or more of water and ethylene glycol, more preferably water.
[0063] In one embodiment, in step (2), the second mixed solution is added by pouring or pumping, preferably by pumping;
[0064] More preferably, the pumping speed is 2 to 20 mL / min.
[0065] The present invention adds a second mixed solution containing a reducing agent to the first mixed solution, and the adding method is preferably pumping. By pumping, the reducing agent in the second mixed solution can fully react with the reactant in the first mixed solution, thereby obtaining high-purity copper nanosheets.
[0066] In one embodiment, in step (2), the reaction temperature is 60-120°C.
[0067] In one embodiment, the molar ratio of the end-capping agent to the copper salt is 1:(2-6), for example, the molar ratio of the end-capping agent to the copper salt may be 1:6, 1:5, 1:4, 1:3, 1:2, etc. In some specific embodiments, when the end-capping agent is CTAB / potassium bromide, the molar ratio of the end-capping agent to the copper salt may be 1:4;
[0068] The molar ratio of the reducing agent to the copper salt is (1-5):1. For example, the molar ratio of the reducing agent to the copper salt can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, etc. In some specific embodiments, when the reducing agent is ascorbic acid, the molar ratio of the reducing agent to the copper salt can be 1.5:1;
[0069] The mass ratio of the copper salt to the protective agent is 1:(0.1-0.6), for example, the mass ratio of the copper salt to the protective agent can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, etc. In some specific embodiments, when the protective agent is PVP, the mass ratio of the copper salt to the protective agent can be 1:(0.2-0.4); when the protective agent is polyethyleneimine, the mass ratio of the copper salt to the protective agent can be 1:(0.4-0.6).
[0070] The molar ratio of the amine substance to the copper salt is 1:(0.25-8). For example, the molar ratio of the amine substance to the copper salt can be 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, etc. In some specific embodiments, when the amine substance is triethylenetetramine, the molar ratio of the amine substance to the copper salt can be 1:3.
[0071] The method of the present invention successfully achieves the regulation of the sheet diameter by controlling the amount of reducing agent and protective agent added. Specifically, the method embodiment uses different types of reducing agents to flexibly adjust the rate of the reduction reaction, and then screens out the best protective agent ratio that matches each reducing agent system to optimize the reaction conditions. This process ensures that each series of reactions can be carried out in the optimal chemical reaction environment, thereby successfully preparing copper nanosheets with different sheet diameter distributions.
[0072] In one embodiment, the method further comprises the following steps:
[0073] (3) washing and drying the prepared copper nanosheets;
[0074] Preferably, the washing comprises washing the prepared copper nanosheets with 5% hydrochloric acid, deionized water and ethanol in sequence; after washing, drying is performed under vacuum or inert gas protection.
[0075] The long-chain end-capping agents commonly used in the prior art (such as dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, oleylamine, oleic acid, etc.) are easily attached to the surface of the product and are difficult to be cleaned by ordinary cleaning agents. They need to be cleaned with organic solvents such as n-hexane and isopropanol, and the treatment process is complicated and the amount of waste is large. However, the present invention uses soluble bromine salt or iodine salt as the end-capping agent, and the prepared copper nanosheets have high cleanliness. The washing can be completed by ordinary cleaning agents (dilute hydrochloric acid, deionized water and ethanol), the process is simple, and the amount of waste is small.
[0076] The present invention also provides a copper nanosheet, which is prepared by the above method.
[0077] In one embodiment, the particle size of the copper nanosheets is 100 nm to 50 μm, preferably 400 nm to 20 μm.
[0078] The present invention realizes flexible adjustment of the particle size of copper nanosheets within the range of 100nm to 50μm by regulating process parameters. For example, the particle size of the prepared copper nanosheets can be 100nm, 400nm, 800nm, 1μm, 2μm, 3μm, 5μm, 7μm, 10μm, 12μm, 13μm, 15μm, 19μm, 20μm, 30μm, 40μm, 50μm, etc. The copper nanosheets prepared by the present invention have regular shapes, uniform particle sizes, and clean surfaces, and can achieve efficient large-scale production.
[0079] The present invention has no special restrictions on the sources of all raw materials. Unless otherwise specified, they are all conventional products that can be obtained commercially.
[0080] The PVP used in the following examples is PVP K-30, and the polyethyleneimine is polyethyleneimine 7w (50% aqueous solution).
[0081] In the following examples, the proportion of 2 copper nanosheets in the product 0 was obtained by SEM analysis.
[0082] Example 1
[0083] The preparation process of the copper nanosheets in this embodiment is as follows Figure 1 As shown, 25g CuSO4·5H2O, 10g PVP, and 3g KBr were dissolved in 200mL ethylene glycol, and the temperature was raised to 100°C. After the temperature stabilized, 60mL of ascorbic acid (28g), NaOH (6g), and ethylenediamine (5g) solution dissolved in water were pumped into the solution at a rate of 4mL / min using a peristaltic pump, and the reaction was continued for 2h. After the reaction was completed, the obtained copper nanosheets were washed with 5% hydrochloric acid, deionized water, and ethanol, and then dried under the protection of inert gas.
[0084] This embodiment prepares copper nanosheets with a sheet diameter of about 19μm. The proportion of copper nanosheets in the product is about 85%, the yield is 98.8%, and the sheet resistivity is 198μΩ·cm. It can be seen from the XRD spectrum that the copper nanosheets prepared in this embodiment have three obvious diffraction peaks, corresponding to the Cu (111) surface, Cu (200) surface and Cu (220) surface, respectively. There are no obvious impurity peaks in the sample, indicating that the purity of the synthesized copper nanosheets is close to 100%. The copper nanosheets prepared in Examples 2 to 8 also obtained similar XRD spectra, which are not listed one by one. SEM and XRD spectra are shown in the figure. Figure 2 and Figure 3 shown.
[0085] Example 2
[0086] 25g CuSO4·5H2O, 10g PVP, 2g CTAB, 2g KBr were dissolved in 200mL ethylene glycol, and the temperature was raised to 100°C. After the temperature stabilized, 60mL of ascorbic acid (28g), NaOH (6g) and triethylenetetramine (5g) solution dissolved in water were pumped into the solution at a rate of 4mL / min using a peristaltic pump, and the reaction was continued for 2h. After the reaction was completed, the obtained copper nanosheets were washed with 5% hydrochloric acid, deionized water, and ethanol, and then dried under inert gas protection.
[0087] In this example, copper nanosheets with a diameter of about 13 μm were prepared. The proportion of copper nanosheets in the product was about 95%, the yield was 96.4%, and the sheet resistivity was 253 μΩ·cm. Figure 4 shown.
[0088] Example 3
[0089] 25g CuSO4·5H2O, 10g PVP, 3g KBr were dissolved in 200mL ethylene glycol, and the temperature was raised to 100°C. After the temperature stabilized, 60mL of ascorbic acid (28g), NaOH (6g), triethylenetetramine (5g) and glucose (5g) solution dissolved in water were pumped into the solution at a rate of 4mL / min using a peristaltic pump, and the reaction was continued for 2h. After the reaction was completed, the obtained copper nanosheets were washed with 5% hydrochloric acid, deionized water, and ethanol, and then dried under inert gas protection.
[0090] In this example, copper nanosheets with a diameter of about 10 μm were prepared. The proportion of copper nanosheets in the product was about 95%, the yield was 96.8%, and the sheet resistivity was 312 μΩ·cm. Figure 5 shown.
[0091] Example 4
[0092] 25g CuSO4·5H2O, 10g PVP, 3g KBr were dissolved in 200mL ethylene glycol, and the temperature was raised to 100°C. After the temperature stabilized, 60mL of ascorbic acid (28g), NaOH (6g), triethylenetetramine (5g) and sodium borohydride (0.5g) solution dissolved in water were pumped into the solution at a rate of 4mL / min using a peristaltic pump, and the reaction was continued for 2h. After the reaction was completed, the obtained copper nanosheets were washed with 5% hydrochloric acid, deionized water, and ethanol, and then dried under the protection of inert gas.
[0093] In this example, copper nanosheets with a diameter of about 7 μm were prepared. The proportion of copper nanosheets in the product was about 87%, the yield was 95.3%, and the sheet resistivity was 423 μΩ·cm. Figure 6 shown.
[0094] Example 5
[0095] 25g CuSO4·5H2O, 10g PVP, 3g KBr were dissolved in 200mL ethylene glycol, and the temperature was raised to 100°C. After the temperature stabilized, 60mL of ascorbic acid (28g), NaOH (6g), triethylenetetramine (5g) and sodium hypophosphite (4g) solution dissolved in water were pumped into the solution at a rate of 4mL / min using a peristaltic pump, and the reaction was continued for 2h. After the reaction was completed, the obtained copper nanosheets were washed with 5% hydrochloric acid, deionized water, and ethanol, and then dried under inert gas protection.
[0096] Example 5: Copper nanosheets with a diameter of about 3 μm were prepared. The proportion of copper nanosheets in the product was about 82%, the yield was 96.9%, and the sheet resistivity was 725 μΩ·cm. Figure 7 shown.
[0097] Example 6
[0098] 25g CuSO4·5H2O, 10g PVP, 3g NH4Br were dissolved in 100mL water, and the temperature was raised to 80°C. After the temperature stabilized, 30mL of ascorbic acid (28g), NaOH (6g) and triethylenetetramine (10g) dissolved in water were pumped into the solution at a rate of 4mL / min using a peristaltic pump, and the reaction was continued for 3h. After the reaction was completed, the obtained copper nanosheets were washed with 5% hydrochloric acid, deionized water, and ethanol, and then dried under inert gas protection.
[0099] Example 6: Copper nanosheets with a diameter of about 10 μm were prepared. The proportion of copper nanosheets in the product was about 90%, the yield was 91.4%, and the sheet resistivity was 312 μΩ·cm. Figure 8 shown.
[0100] Example 7
[0101] 25g CuSO4·5H2O, 10g polyethyleneimine, and 3g KBr were dissolved in 100mL water, and the temperature was raised to 80°C. After the temperature stabilized, 30mL of ascorbic acid (28g) and NaOH (6g) dissolved in water were pumped into the solution at a rate of 4mL / min using a peristaltic pump, and the reaction was continued for 3h. After the reaction was completed, the obtained copper nanosheets were washed with 5% hydrochloric acid, deionized water, and ethanol, and then dried under inert gas protection.
[0102] Example 7: Copper nanosheets with a sheet diameter of about 12 μm were prepared. The proportion of copper nanosheets in the product was about 82%, the yield was 99.8%, and the sheet resistivity was 229 μΩ·cm. Fig. 9 shown.
[0103] Example 8
[0104] 25g CuSO4·5H2O, 5g PVP, 10g ammonia (mass fraction 25% to 28%), and 3g KBr were dissolved in 100mL water, and the temperature was raised to 80°C. After the temperature stabilized, 30mL of ascorbic acid (28g) and NaOH (6g) dissolved in water were pumped into the solution at a rate of 4mL / min using a peristaltic pump, and the reaction was continued for 3h. After the reaction was completed, the obtained copper nanosheets were washed with 5% hydrochloric acid, deionized water, and ethanol, and then dried under inert gas protection.
[0105] Example 8: Copper nanosheets with a sheet diameter of about 8 μm were prepared. The proportion of copper nanosheets in the product was about 90%, the yield was 95%, and the sheet resistivity was 324 μΩ·cm. Fig.10 shown.
[0106] It can be seen from the above examples that the method for preparing copper nanosheets of the present invention has the following significant advantages:
[0107] The production cost is low, and the raw materials used in the present invention are widely available and easy to obtain, thereby greatly reducing the production cost, making the method economically very competitive.
[0108] The process is simple, and copper nanosheets with different sheet diameters are prepared by controlling different reduction systems; it is green and environmentally friendly, and the selection of environmentally friendly solvents and the use of halogen ions significantly reduce environmental pollution and waste emissions in the production process.
[0109] The preparation efficiency is high, and the complete reaction of 25g of raw material CuSO4·5H2O can be completed in only 2 to 3 hours, and the amount of solvent used is small, and the prepared copper nanosheets have high cleanliness.
[0110] Regarding the evaluation of the surface cleanliness of copper powder, the present invention uses a precision powder resistivity tester for testing. The test process specifically involves the following steps: first, a pressure of 300kg is applied to a 0.5g copper powder sample, and a constant pressure is maintained for 30s to prepare a pressed sheet; then, the resistivity of the pressed sheet (unit: μΩ·cm) is measured as a standard for evaluating the surface cleanliness of the copper powder. In theory, the cleanliness of the copper powder surface is directly related to its conductive properties: when the surface cleanliness reaches a high level, the copper powder particles can be in closer and direct contact, so that it is easy to form a conductive path, resulting in a significant decrease in the resistivity after the pressed sheet. On the contrary, if the surface cleanliness of the copper powder is not good, there are impurities such as organic matter, which will hinder the direct contact between the copper powder particles, increase the obstacles to electron transmission, and thus significantly increase the resistivity of the pressed sheet. Therefore, the measurement results of the powder resistivity tester can accurately reflect the cleanliness of the copper powder surface and its impact on the conductive properties. The copper nanosheets prepared by the preparation method provided by this patent have an average sheet resistivity of about 400 μΩ·cm, which is significantly lower than the sheet resistivity of commercially available copper nanosheets (1.67×10 7 μΩ·cm). Therefore, it can be clearly stated that the copper nanosheets prepared by the present invention not only have good electrical conductivity but also high cleanliness.
[0111] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. A method for preparing copper nanosheets, comprising: (1) dissolving a copper salt, a protective agent, and a capping agent in a first solvent to obtain a first mixed solution; (2) adding a reducing agent to the first mixed solution to react, and the ratio of copper nanosheets in the obtained product is 80% to 99%; Wherein, the capping agent is a soluble bromide salt or iodine salt.
2. The method according to claim 1, characterized in that In step (1), the copper salt is selected from one or more of CuSO4·5H2O, Cu(NO3)2·3H2O, CuCl2, CuBr2, and Cu(HCOO)2·4H2O; In step (1), the protective agent is a surfactant, preferably one or more selected from PVP, polyethyleneimine, and polyethylene glycol; In step (1), the first solvent is alcohol and / or water, preferably ethylene glycol and / or water; and / or In step (2), the reducing agent is selected from one or more of ascorbic acid, glucose, sodium hypophosphite, sodium borohydride, and hydrazine hydrate.
3. The method according to claim 1 or 2, characterized in that: Step (2) further includes adding an amine substance and / or a base to the first mixed solution; Preferably, the amine substance is selected from one or more of triethylenetetramine, diethylenetriamine, tetraethylenepentamine, isopropanolamine, oleylamine, ethylenediamine, ethanolamine, polyethyleneimine, triethylenediamine, 2-amino-2-methyl-1-propanol, and ammonia water; and / or Preferably, the base is selected from one or more of NaOH and KOH, more preferably NaOH.
4. The method according to any one of claims 1 to 3, characterized in that In step (2), the reducing agent, the optional amine substance, and the optional base are dissolved in a second solvent to obtain a second mixed solution, and then the second mixed solution is added to the first mixed solution; Preferably, the second solvent is one or more of water and ethylene glycol, more preferably water.
5. The method according to claim 4, characterized in that In step (2), the second mixed solution is added by pouring or pumping, preferably by pumping; More preferably, the pumping speed is 2 to 20 mL / min.
6. The method according to claim 4 or 5, characterized in that: In step (2), the reaction temperature is 60-120°C.
7. The method according to any one of claims 1 to 6, characterized in that The molar ratio of the end-capping agent to the copper salt is 1:(2-6); The molar ratio of the reducing agent to the copper salt is (1-5):1; The mass ratio of the copper salt to the protective agent is 1:(0.1-0.6); The molar ratio of the amine substance to the copper salt is 1:(0.25-8).
8. The method according to any one of claims 1 to 7, characterized in that The method further comprises the following steps: (3) washing and drying the prepared copper nanosheets; Preferably, the washing comprises washing the prepared copper nanosheets with 5% hydrochloric acid, deionized water and ethanol in sequence; after washing, drying is performed under vacuum or inert gas protection.
9. A copper nanosheet, characterized in that: The copper nanosheets are prepared by the method according to any one of claims 1 to 8.
10. The copper nanosheet according to claim 9, characterized in that: The particle size of the copper nanosheets is 100 nm to 50 μm, preferably 400 nm to 20 μm.